PENGARUH E-WOM, KREDIBILITAS LABEL, DAN KREDIBILITAS INFLUENCER TERHADAP MINAT BELI KONSUMEN STUDI KASUS PADA INDUSTRI KOSMETIK DAN LABEL “TASYA FARASYA APPROVED” - Putri, Syafira Ramadhanti; Wulandari , Nuri (Journal of Accounting, Management and Islamic Economics, 2024)
This study aims to analyze the influence of Electronic Word of Mouth (E-WOM), label credibility, and influencer credibility on consumer purchase intention in the cosmetics industry, focusing on the "Tasya Farasya Approved" label. The main issue addressed is the extent to which the "Tasya Farasya Approved" label impacts consumer purchase intention for cosmetic products. The research method uses a quantitative approach, with data collected through questionnaires distributed to consumers who use cosmetics with this label. The results indicate that influencer credibility has a positive and significant effect on consumer purchase intention. These findings highlight the importance of an influencer's credibility in influencing consumer purchasing decisions and demonstrate the potential of a special label issued by an influencer to strengthen product image in the cosmetics industry.